Pemahaman Teoritis Pembiayaan Pendidikan: Peran dan Ragam Jenis Pembiayaan dalam Meningkatkan Sistem Pendidikan di Indonesia - Rizkia Apriani (Journal of Public Policy Analys, 2024)
Education is a key pillar of development, but Indonesia still faces challenges in the accessibility, quality, and relevance of education to the needs of the job market. One of the main problems is the low quality of education, which is influenced by the lack of facilities and qualified teaching staff. The ineffective use of education financing, such as in teacher training and procurement of facilities, is one of the causes. This study aims to identify and analyze the types of education financing in Indonesia and their role in improving the quality of education. Using a qualitative approach with a literature research method, this study examines written documents, including books, scientific articles, and policy reports related to education financing. The results of the study show that education financing can be grouped into direct and indirect costs, routine and development costs, and personal and community costs. All of these costs support each other in creating quality and sustainable education. This research is expected to make a practical contribution to policymakers, educators, and the community in optimizing education financing for better human resource development in Indonesia.